DESKRIPSI PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK PADA PENERAPAN MODEL PEMBELAJARAN GENERATIF KELAS XI MIPA SMAN 1 PASAMAN - Jevi Melia Putri (Departemen Matematika, 2021)
Understanding mathematical concepts is a very important part in learning mathematics because it is one of the goals of learning mathematics that must be achieved by students. But in fact, the understanding of mathematical concepts of students in class XI MIPA SMAN 1 Pasaman is still low. One of the efforts that can be done to improve students' understanding of mathematical concepts is by applying a generative learning model. This research aims to describe the understanding of mathematical concepts of students who apply the generative learning model in class XI MIPA SMAN 1 Pasaman. This type of research is Pre-experiment with One Shot Case Study design. The subjects of this study were students of class XI MIPA SMAN 1 Pasaman for the academic year 2021/2022 with class XI MIPA 2 Shift A as the subject class. The research instrument is a test of understanding mathematical concepts in the form of essay questions which are analyzed by looking for the class average of the subject then qualified. Based on data analysis, it was found that the average result of the students' mathematical concept understanding test in the subject class was 23.50. After the average is qualified, it is obtained that the understanding of the mathematical concepts of students who learn by applying the generative learning model is in the high category. Keywords– understandings of mathematics concepts, Generative Learning Model, Pra-Experiment